PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA - Zainuddin, Muhammad; Prayogi, Saiful; Gummah, Syifaul (Jurnal Ilmiah IKIP Mataram, 2019)
This study aims to improve the activity and achievement of students in grade VIII MTs. NW Sikur. The type of research used is classroom action research in the form of observation sheet and evaluation evaluation test. This research is an AR consisting of: (1) planning, (2) implementation of action, (3) observation (observation), and (4) reflection. The results showed an increase in activity and student achievement in cycle I of 2.26 with category (quite active), while in cycle II amounted to 3.84 with the category (active). In the first cycle the average value of student learning outcomes is 75.46 with the percentage of classical completeness 80.76%, and an increase in cycle II to 79.07 with the percentage of classical completeness 88.46%. The conclusion that the use of Think Pair Share method on the subject of physics affects student activity and achievement.